Personal Identity and the Possibility of Autonomy. (7th November 2017) - Hershenov, David B.; Taylor, Adam P.
Abstract: We argue that animalism is the only materialist account of personal identity that can account for the autonomy that we typically think of ourselves as possessing. All the rival materialist theories suffer from a moral version of the problem of too many thinkers when they posit a human person that overlaps a numerically distinct human animal. The different persistence conditions of overlapping thinkers will lead them to have interests that conflict, which in many cases prevents them both from autonomously forming and acting on the same intentions. These problems are exacerbated by problems of self‐reference plaguing the overlapping thinkers. We contend that the impossibility of simultaneous autonomous action by animals and persons provides a reason to favor animalism over Neo‐Lockeanism, Four‐Dimensionalism, Constitution theory, and brain‐size views of the person. We anticipate and reject arguments that the autonomy of the person and the animal can be shown to be compatible by relying upon either the Parfitian thesis that identity isn't what matters or claiming that animals acquire the interests of the person they constitute.